Perancangan Tracer/Out Guide Berkas Rekam Medis di Puskesmas - Sitti Budiaty, Wa Ode; Latumbu, Sumpia (Politeknik Baubau, 2022)
Design of trace/out guide Medical Record at Puskesmas Wolio, Baubau city in 2021 with research methods with a phenomenological approach. Based on the initial data collection which was carried out at the Wolio Health Center On june 5, 2021, the design of a tracer in the medical record filing section at the Wolio Health Center is very necessary in order to minimize the occurrence of Misfiles that oflen occur in the medical record filing section. The research objective is to design a tracer/out guide for medical record files that can be used at the Wolio Health Center, Baubau City. The subjects in this study were 3 medical record officers at the patient registration and filing department. The results of this study are the patient comes back then the officer looks for the register folder which turns out to be not there. Of the four tracer design drafts that have been designed for the chose a tracer design made from Poly Ethylene Terphthalate (PET) alternative 1 with consideration of the thin material so that it can be used on shelves that are full or solid and the material is elastic so that it can be used repeatedly in long period of time.